Health education on prevention of sexually transmitted infections: case studies / Educação em saúde na prevenção de infecções sexualmente transmissíveis: relato de experiência - Jéfferson dos Santos; Byhanca Halyne Ferreira dos Santos (); Marina Ellen de Oliveira Barbosa; Thayse Barbosa Sousa Magalhães; Francisca Maria Nunes da Silva; Rosa Patrícia Gomes Tenório Omena Rodrigues (Universidade Estadual de Alagoas, 2019)
The case studies carried out by academics of nursing course at the Federal University of Alagoas Arapiraca Campus. From our experience in the field by means of an extension project where the focus is directed to the prevention of sexually transmitted Infections, associating cervical lesions. For community outreach, so us the practice of health education, tool that allowed us to approach and confidence with women, allowing us through the wheels of conversation, spread the knowledge through statements that favored an active communication with your body. Favouring in this way a trust and rapprochement with the assistance.